The effect of policy implementation, management of border areas, relations between government and community welfare to security effectiveness in the border area of Indonesia-Malaysia (A study of Nunukan Regency, North Kalimantan Province) - Makmur Makmur (International Journal Labs, 2025)
This research examines the security challenges in the Indonesia-Malaysia border area, particularly in Nunukan Regency, North Kalimantan Province. The study aims to assess the influence of policy implementation, border area management, intergovernmental relations, and community welfare on security effectiveness. Using a quantitative approach, data were collected through surveys with Likert scale questionnaires, focusing on the perception of respondents regarding the stated variables. The findings reveal that effective policy implementation, sound border management, strong intergovernmental relations, and improved community welfare significantly enhance security effectiveness in the region. Specifically, these factors collectively account for 60.2% of the variations in security effectiveness, indicating their critical role in addressing security concerns. The implications of this research suggest that comprehensive strategies involving all stakeholders are necessary to improve security outcomes. Recommendations include enhancing policy implementation, fostering cooperation between governments, and promoting community welfare to create a supportive environment for security initiatives. Overall, the study contributes valuable insights for policymakers and local authorities in improving security and welfare in border areas, emphasizing the need for integrated approaches to manage complex border dynamics effectively.